Gastric cancer prevention from the point of helicobacter - Balaban, Yasemin Hatice; Şimşek, Halis; Tatar, Gonca (AVES, 2014)
When the first cancer estimates of world were made in 1975, gastric cancer (GC) was the most common neoplasm, making 70% of the total. Although its rate decreased to 6.8% in 2012, it is still the fifth most common malignancy after cancers of the lung, breast, colo-rectum, and prostate and the third leading cause of cancer death in both sexes worldwide (8.8%, 723,000 deaths) (1). Proximal (cardia) and distal (non-cardia) gastric adenocarcinomas have different epidemiological and clinical features. Although there is an increase in proximal GCs, most of the GCs are still distally located, and intestinal-type. H. pylori is an established trigger of gastric carcinogenesis; reversibility of precancerous conditions, including intestinal metaplasia (IM), after eradication treatment is a hot topic for research. Therefore, we read with great interest the study by Galiatsatos P et al. (2) on the sensitivity of gastric biopsy for H. pylori detection in the presence of IM. The data have once again emphasized the importance of using non-invasive tests and histopathology together in the presence of gastric IM.
WOS: 000345025900038
PubMed ID: 25254545
Keywords: Gastric Cancer; Helicobacter